Immunorehabilitation Children with Impaired Health Status - O. V. Shamsheva; I. V. Poleskо (Детские инфекции (Москва))
Polyoxidonium® — domestic drug with a broad spectrum of pharmacological action, which is unparalleled in the world. The drug is used as an immunomodulator, detoksikant, immunostimulatory and sustained release carrier of pharmacologically active compounds. Currently collected convincing evidence base safe and effective use Polyoxidonium for respiratory diseases with severe severity of symptoms, including in children with a poor premorbid background (often ill children, chronic lymph adenotonzillit pathology of allergic disease), are at risk of complicated infection (ARI suppurative complications in history), the formation of prevention programs and immunoreabilitatsionnyh children with recurrent respiratory infections.